2019
DOI: 10.1007/s41918-019-00060-4
|View full text |Cite
|
Sign up to set email alerts
|

Building Safe Lithium-Ion Batteries for Electric Vehicles: A Review

Abstract: Lithium-ion batteries (LIBs), with relatively high energy density and power density, have been considered as a vital energy source in our daily life, especially in electric vehicles. However, energy density and safety related to thermal runaways are the main concerns for their further applications. In order to deeply understand the development of high energy density and safe LIBs, we comprehensively review the safety features of LIBs and the failure mechanisms of cathodes, anodes, separators and electrolyte. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
301
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 594 publications
(301 citation statements)
references
References 281 publications
(402 reference statements)
0
301
0
Order By: Relevance
“…In addition, it is found that PVDF might react with the lithiated graphite or lithium metal at high temperatures (above 45 °C) to form LiF and unsaturated >CCF bonds with resultant heat release, leading to potential safety issues. [10,13] Especially when cycled at high C rates, the lithium-ion conductivity of graphite/PVDF electrode is not high enough to accommodate the fast intercalation of Li + ; the unsettled Li + would then deposit on the surface of graphite, leading to dead lithium and safety concerns.…”
Section: Graphitementioning
confidence: 99%
“…In addition, it is found that PVDF might react with the lithiated graphite or lithium metal at high temperatures (above 45 °C) to form LiF and unsaturated >CCF bonds with resultant heat release, leading to potential safety issues. [10,13] Especially when cycled at high C rates, the lithium-ion conductivity of graphite/PVDF electrode is not high enough to accommodate the fast intercalation of Li + ; the unsettled Li + would then deposit on the surface of graphite, leading to dead lithium and safety concerns.…”
Section: Graphitementioning
confidence: 99%
“…It should be noted that the most efficient LiFePo4 batteries currently on the market have densities of 0.25 KWh/kg and 0.62 KWh/L respectively. Current research to improve battery performance focuses on the one hand on the nature and shape of the electrodes and on the other hand on the conductivity ionic of the electrolyte and the separator, for a larger storage capacity, more stability and larger operating temperature ranges [34]. In particular, the electrolyte can be liquid or solid.…”
Section: Study Casementioning
confidence: 99%
“…Their discharge voltage is more stable and they present a lower fire risk. The technology is mature and has an average cost of between 6400 and 13,600e /ton, which places it among the cheapest on the market for current lithium batteries [34]. It can thus be estimated that a 20,000-ton (1600 evp) ship would require between 625 and 1250 MWh to travel 1000 km at sea and occupy the volume of 80 to 160 evp.…”
Section: Study Casementioning
confidence: 99%
“…[ 10–12 ] From these works, the application prospect of ASSBs has been restricted by some critical problems: 1) large resistance caused by poor contact and space charge layer generated in the interface inside the ASSBs; 2) the cell failure due to alkali metal dendrite growth; 3) poor interface stability between electrode and solid electrolyte (SE), which leads to inferior cycle performance of ASSBs. [ 1,13–16 ] Thus, the interface dominates the performance of ASSBs.…”
Section: Introductionmentioning
confidence: 99%